2015
DOI: 10.1093/qjmam/hbv007
|View full text |Cite
|
Sign up to set email alerts
|

Active cloaking of inclusions for flexural waves in thin elastic plates

Abstract: We present a new method to create an active cloak for a rigid inclusion in a thin plate, and analyse flexural waves within such a plate governed by the Kirchhoff plate equation. We consider scattering of both a plane wave and a cylindrical wave by a single clamped inclusion of circular shape. In order to cloak the inclusion, we place control sources at small distances from the scatterer and choose their intensities to eliminate propagating orders of the scattered wave, thus reconstructing the respective incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Note that in this particular case A (e) n = i n since 15) and the B (e) n are identically zero. It can be shown that the general expression for the scattered field is (see, for example, [18], [21], [22])…”
Section: Multipole Representation For a Plane Wave Scattered By A Coamentioning
confidence: 99%
See 2 more Smart Citations
“…Note that in this particular case A (e) n = i n since 15) and the B (e) n are identically zero. It can be shown that the general expression for the scattered field is (see, for example, [18], [21], [22])…”
Section: Multipole Representation For a Plane Wave Scattered By A Coamentioning
confidence: 99%
“…9 that the multipole field components of higher order become non-negligible, and hence passive reduction of scattering would not be appropriate any longer. Active cloaking by point sources, as described in [18], enables us to make the multipole coefficients vanish to the required order.…”
Section: Passive Control Of Scattering By An Appropriate Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…This gave birth to the subject of active exterior cloaking for conductivity [48,52], for acoustics in twodimensions and three-dimensions [48,49,51,53,129] and for elastodynamics [130]. In a beautiful twist of the idea, O'Neill, Selsil, McPhedran, Movchan, Movchan, and Moggach [133,134] found that for the plate equation one could get excellent exterior cloaking without enormous fields if one relaxed the requirement that the cloak create a quiet zone and instead require only that it cloak a given object. The main reason that enormous fields are not needed is that the plate equation has the desirable property that the Green's function is bounded.…”
Section: Discovery Of a Ghost Sourcementioning
confidence: 99%
“…Recently, materials having negative physical constants were discovered. It concerns dielectric-magnetic materials displaying a negative index of refraction [1,2,9,23,24]. Mathematical modelling of metamaterials and neutral (invisible) inclusions were discussed in [12,14,17] and works cited therein.…”
Section: Introductionmentioning
confidence: 99%